FRI0022 Periodontal pathogens promote autoimmune arthritis by reducing TH2 response and inducing a toll-like receptor 2-dependent TH17 phenotype. (23rd January 2014) - Abdollahi-Roodsaz, S.; Garcia de Aquino, S.; Koenders, M.; Marijnissen, R.; Walgreen, B.; Helsen, M.; van den Bersselaar, L.; de Queiroz Cunha, F.; Cirelli, J.A.; van den Berg, W.
Abstract : Background: Epidemiologic evidence and the capability of periodontal pathogen Porphyromonas gingivalis to citrullinate mammalian proteins support a link between periodontal disease (PD) and rheumatoid arthritis (RA). Based on the relevance of pathogen-mediated Toll-like receptor (TLR) activation in shaping the T cell response, we reasoned that the interaction between PD and RA may be a direct result of T cell modulation and not necessarily dependent on citrullination capability. Objectives: The aim of this study was to investigate the influence of periodontal pathogens P. gingivalis and Prevotella nigrescens, the latter lacking citrullinating enzymes, on T helper cell phenotype and the development of experimental arthritis. Methods: The influence of P. gingivalis and P. nigrescens on T cell differentiation and the TLR involvement were studied using wild-type, and interleukin-1 receptor antagonist (IL-1Ra)/TLR single or double gene deficient cells. In vivo, mice with collagen-induced arthritis received five oral inoculations of either P. gingivalis or P. nigrescens every other day starting from day 14 after immunization. Joint histopathology, synovial gene expression, T cell phenotype and presence of anti-citrullinated peptide antibodies (ACPA) were analyzed on day 30. Results: P. gingivalis and P. nigrescens strongly induced Th17 differentiation in a co-culture of antigen-presenting cells (APCs) with CD4 + T cells, as measured by FACS and IL-17 production. This effect was highly increased by IL-1Ra deficiency. In addition, both bacteria significantly lowered the Th2 differentiation, but were weak inducers of Th1. Using IL-1Ra -/- TLR2 -/- cells, Th17 induction was found to depend on TLR2 expression on APCs; whereas the minor Th1 induction was dependent on TLR2 expression directly on T cells. TLR4 activation was not involved in Th17 differentiation induced by these bacteria. In vivo, oral inoculation with P. gingivalis and P. nigrescens significantly increased the clinical arthritis scores. Although no antibodies against cyclic citrullinated peptide (CCP)-2, citrullinated fibrinogen, a-enolase and vimentin could be detected under this condition, both bacteria substantially increased the severity of bone erosion. Collagen II stimulation of draining lymph node T cells revealed that P. gingivalis as well as P. nigrescens significantly increased antigen-specific IL-17, but not IFNγ, production. This IL-17 production strongly correlated with the intensity of bone erosion. In addition, P. nigrescens markedly suppressed the anti-inflammatory Th2/IL-4 phenotype in vivo, whereas P. gingivalis was the main inducer of local IL-1b, TNFa and Cathepsin K in synovium. Conclusions: These data reveal a substantial effect of periodontal pathogens, irrespective of the capability to induce ACPA, on T cell phenotype in the context of arthritis with a remarkable impact on bone erosion. This study further supports the relevance of periodontal pathogens in the pathogenesis of RA. Disclosure of Interest: None Declared